Pemetrexed Ameliorates Experimental Arthritis in Rats - Karatas, Ahmet; Koca, Suleyman Serdar; Ozgen, Metin; Dagli, Adile Ferda; Erman, Fazilet; Sahin, Nuran; Isik, Ahmet (Springer/Plenum Publishers, 2015)
Pemetrexed (PMTX) is an anti-folate drug as methotrexate. The purpose of this study was to assess the efficacy of PMTX on collagen-induced arthritis (CIA). Forty Wistar albino rats were randomized into four groups. Arthritis was induced by intradermal injection of chicken type II collagen combined with incomplete Freund's adjuvant. Animals were sacrificed at the 15th day after the onset of arthritis. Tumor necrosis factor alpha (TNF-alpha), interleukin (IL)-17, and malondialdehyde (MDA) levels were increased, and superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities and the expressions of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) were decreased in the arthritis group. In the PMTX-treated (0.2 and 1 mg/kg/week i.p.) groups, the levels of TNF-alpha, IL-17, and MDA were decreased; the activities of SOD, CAT, and GPx and the expressions of Nrf2 and HO-1 were restored, and perisynovial inflammation and cartilage-bone destruction were decreased. PMTX has anti-arthritic potential in the CIA model and may be a therapeutic agent for rheumatoid arthritis.
Keywords: rheumatoid arthritis; collagen; induced arthritis; pemetrexed